URGENSI PEMBAHARUAN HUKUM AUTOPSI DALAM PROSES PENYIDIKAN TINDAK PIDANA PEMBUNUHAN UNTUK MENCAPAI KEBENARAN MATERIIL - Naufal, Rifki Shofwan; Rusmiati, Elis; Ramdan, Ajie (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
The functions of forensic autopsy in murder investigation process is to examine the victim’s body and provide definite informations about the victim’s death. Forensic autopsy results will be used by Investigators as an evidence that can prove causal verband between the actions of the suspect and the death of the victim. But there are problems, incomplete autopsy regulation which results in uncertainty along with irregularities in the autopsy process in practice and the second problem is the autopsy function in the process of investigating the crime of murder in an effort to find and achieve material truth. Unclear and incomplete regulations related to autopsy caused unclear interpretation of the regulations regarding autopsy also differences in relation to application in investigation practice. The rule of forensic autopsy will affect the function of autopsy as the main examination standard to examines cause of death to achieve the truth of victim’s death. The renewal rule of forensic will be first step to optimize the development of forensic autopsy according to field requirements and to optimize the function of autopsy, so it will have the effect of reducing doubts on the disclosure of murder cases.